(untitled) (Brazilian Journal of Health Research, 2025)
Introduction: Davy Lucas Cândido Rodrigues, nearly four years old, died after being left at an urgent care facility following sexual abuse perpetrated by his stepfather. Objective: This study aims to understand the unfolding of the intrafamilial dimension of child sexual violence, as well as gender- and age-related aspects, based on journalistic content. Methods: Through bibliographic and documentary research, using exploratory and descriptive methods, the study brings the academic literature into dialogue with legislation and published news reports, in order to classify the case of the abused boy as another situation of power relations between adults and children. Results: The findings reinforce the presence of power dynamics between the stepfather and the child, situating the case within the scope of intrafamilial child sexual violence, while also pointing to traces of gender and age oppression. Conclusion: It is concluded that Davy was yet another victim of a historical and social problem, embedded in relational dynamics marked by power usurpation, which demands effective strategies for the prevention and confrontation of child sexual violence.